Navigating the 16-dimensional Hilbert space of a high-spin donor qudit with electric and magnetic fields - Irene Fernández de Fuentes; Tim Botzem; Mark A. I. Johnson; Arjen Vaartjes; Serwan Asaad; Vincent Mourik; Fay E. Hudson; Kohei M. Itoh; Brett C. Johnson; Alexander M. Jakob; Jeffrey C. McCallum; David N. Jamieson; et al. (Nature Communications, 2024)
Abstract Efficient scaling and flexible control are key aspects of useful quantum computing hardware. Spins in semiconductors combine quantum information processing with electrons, holes or nuclei, control with electric or magnetic fields, and scalable coupling via exchange or dipole interaction. However, accessing large Hilbert space dimensions has remained challenging, due to the short-distance nature of the interactions. Here, we present an atom-based semiconductor platform where a 16-dimensional Hilbert space is built by the combined electron-nuclear states of a single antimony donor in silicon. We demonstrate the ability to navigate this large Hilbert space using both electric and magnetic fields, with gate fidelity exceeding 99.8% on the nuclear spin, and unveil fine details of the system Hamiltonian and its susceptibility to control and noise fields. These results establish high-spin donors as a rich platform for practical quantum information and to explore quantum foundations.